Pengembangan Media Pembelajaran TIC TAC TOE berbasis Problem Based Learning Untuk Meningkatkan Motivasi Belajar Pendidikan Pancasila Kelas VB MIN 2 Kota Padang - Lici Anjona; Sekar Harum Pratiwi; Dini Susanti (PT Suria Academic Press, 2026)
The development of learning media used by teachers in class VB of MIN 2 Padang City is still not optimal in utilizing learning media. The media used consists of picture posters, causing students to be less active and bored during learning. To overcome this problem, Tic Tac Toe Learning Media was developed to fulfill students' learning needs and increase their learning motivation. This research employed R&D with the ADDIE model. This research also applied the PBL model. The developed material covers the Diversity of Indonesian Culture in Pancasila Education subject during the even semester. The validity of the Tic Tac Toe product was tested by validators using a validity questionnaire. Practicality was assessed by teachers, while effectiveness was evaluated by 29 students through an effectiveness questionnaire. Based on the research results, this media successfully increased the learning motivation of students in class VB of MIN 2 Padang City. Teachers can also utilize this media to enhance students' enthusiasm and motivation in learning Pancasila Education. The assessment results indicate that three aspects were fulfilled. Meanwhile, validity aspect obtained a score of 90% with a very valid category. The practicality aspect achieved a score of 78.3%, categorized as practical. The effectiveness aspect received a score of 90.2%, classified as very effective.